1997
DOI: 10.1002/art.1780401206
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of synovial cell function by somatostatin in patients with rheumatoid arthritis

Abstract: Objective. To elucidate the role of neurologic, endocrine, and immune system interactions in the development of pathologic responses in patients with rheumatoid arthritis (RA), we studied somatostatin (SOM) production and somatostatin receptor (SOMR) expression in RA synovium and its function in patients with RA.Methods. The effects of SOM on proinflammatory cytokine (interleukin-6 [IL-6] and IL-8) and collagenase production by RA synovial cells were estimated by enzyme-linked immunosorbent assay, and their me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 46 publications
0
45
2
Order By: Relevance
“…In our studies we did not observe a reduction in the severity of rat adjuvant arthritis using the SRIF analogue octreotide (ten Bokum et al, 1999b). Takeba et al has shown that SRIF at physiological concentrations inhibits the in vitro proliferation of fibroblast-like synovial cells from RA patients (Takeba et al, 1997). Cultured fibroblast-like synovial cells express mRNA for both sst 1 and sst 2 , while sst 2 mRNA is sensitive to upregulation by proinflammatory stimuli.…”
Section: Small-molecule Ghs Has a Considerable Immune-enhancing Effeccontrasting
confidence: 54%
See 1 more Smart Citation
“…In our studies we did not observe a reduction in the severity of rat adjuvant arthritis using the SRIF analogue octreotide (ten Bokum et al, 1999b). Takeba et al has shown that SRIF at physiological concentrations inhibits the in vitro proliferation of fibroblast-like synovial cells from RA patients (Takeba et al, 1997). Cultured fibroblast-like synovial cells express mRNA for both sst 1 and sst 2 , while sst 2 mRNA is sensitive to upregulation by proinflammatory stimuli.…”
Section: Small-molecule Ghs Has a Considerable Immune-enhancing Effeccontrasting
confidence: 54%
“…In biopsies of rheumatoid synovium sst 2 expression has been detected on macrophages, as well as on endothelial cells of venules (especially high endothelial venules) (Takeba et al, 1997;ten Bokum et al, 1999a;Vanhagen et al, 1994a). SRIF can be produced by synovial cells or secreted by sensory nerve endings into the joint capsule (Takeba et al, 1997). These data point towards the existence of a SRIF immunoregulatory circuit within the rheumatoid synovium.…”
Section: Small-molecule Ghs Has a Considerable Immune-enhancing Effecmentioning
confidence: 99%
“…Besides the earlier mentioned correlation between inflammation and uptake of radiolabelled octreotide in scintigraphy (19), it was also demonstrated that somatostatin inhibits both proliferation of synovial cells from patients with rheumatoid arthritis and production of the pro-inflammatory cytokines IL-6 and IL-8 (40). Notably, these authors also report the presence of sst 1 and sst 2 on fibroblast-like synovial cells and the absence of receptors on T-lymphocytes.…”
Section: Detection Of Sst 2a In Human Immune Diseases By Immunohistocmentioning
confidence: 69%
“…In RA patients, somatostatin receptors have been detected in the synovial tissue of affected joints (39,40). Activation of these receptors using SRIF-14 inhibited the proliferation of synovial cells from RA patients in vitro (41). However, our knowledge about the somatostatin receptor subtypes involved in the antiinflammatory and antinociceptive actions of SRIF-14 is limited.…”
Section: Discussionmentioning
confidence: 99%